When do contrast sensitivity deficits (or enhancements) depend on spatial frequency? Two ways to avoid spurious interactions. (26th December 2022) - Bi, Howard; Abrham, Yonatan; Butler, Pamela D.; Hu, Boyang; Keane, Brian P.
Abstract: Studies across a broad range of disciplines—from psychiatry to cognitive science to behavioural neuroscience—have reported on whether the magnitude of contrast sensitivity alterations in one group or condition varies with spatial frequency. Significant interactions have often gone unexplained or have been used to argue for impairments in specific processing streams. Here, we show that interactions with spatial frequency may need to be re‐evaluated if the inherent skew/heteroscedasticity was not taken into account or if visual acuity could plausibly differ across groups or conditions. By re‐analysing a publicly available data set, we show that—when using raw contrast sensitivity data—schizophrenia patients exhibit an apparent contrast sensitivity impairment that lessens with spatial frequency, but that when using log‐transformed data or when using generalized estimating equations, this interaction reversed. The reversed interaction, but not the overall contrast sensitivity deficit, disappeared when groups were matched on visual acuity. An analysis of the contrast threshold data yielded similar results. A caveat is that matching groups on acuity is probably only defensible if acuity differences arise from non‐neural factors such as optical blur. Taken together, these analyses reconcile seemingly discrepant findings in the literature and demonstrate that reporting contrast sensitivity interactions with spatial frequency requires properly accounting for visual acuity and skew/heteroscedasticity. Abstract : Special population studies of contrast sensitivity commonly report group differences that vary with spatial frequency. We show that the direction and statistical significance of such interactions strongly depend on whether the data are log transformed and whether groups are matched on acuity. This demonstration reconciles seemingly conflicting findings in the literature and suggests ways to avoid misinterpreting spatial frequency interactions.